Strategi Inggris Raya Terhadap Permasalahan Industri Agrikultur Pasca Brexit - Majid, Azam Abdil; Putri, Sindy Yulia; Astuti, Wiwiek Rukmi Dwi (University of Jember, 2023)
Brexit has restricted the flow of migrant workers in the industrial sector and agricultural system in the United Kingdom. This research examines the dynamics of the agricultural industry issues in the United Kingdom, as well as the strategies implemented by the UK government to minimize the issues faced in the agricultural sector. The methodology employed is qualitative, utilizing theories of international migration and concepts of international immigration policy. The UK Government has implemented strategies to minimize the agricultural issues after Brexit. These strategies include implementing seasonal worker visas, adopting a points-based immigration system, formulating the agricultural act 2020, promoting local workers, and embracing automation. These strategies have successfully minimized the issues in the agricultural industry in the United Kingdom.